3(4P+1)-2=49

Simple and best practice solution for 3(4P+1)-2=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4P+1)-2=49 equation:


Simplifying
3(4P + 1) + -2 = 49

Reorder the terms:
3(1 + 4P) + -2 = 49
(1 * 3 + 4P * 3) + -2 = 49
(3 + 12P) + -2 = 49

Reorder the terms:
3 + -2 + 12P = 49

Combine like terms: 3 + -2 = 1
1 + 12P = 49

Solving
1 + 12P = 49

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 12P = 49 + -1

Combine like terms: 1 + -1 = 0
0 + 12P = 49 + -1
12P = 49 + -1

Combine like terms: 49 + -1 = 48
12P = 48

Divide each side by '12'.
P = 4

Simplifying
P = 4

See similar equations:

| 357(x-2)=255x | | 3-4d=13 | | -12+4n=-3(2-2n) | | 12-3x=-6 | | -(3n+4)=-2n-2 | | -14x-20=-12x+70 | | 8+-38=-30 | | -2(6b+1)=34-6b | | 4(1-6v)-6v=-5v-21 | | V+3-5=-2 | | 4m-6+4=2 | | 2k+34=-2(2k+4) | | 2a+12=31-3a | | 4-4(4N+4)=52 | | -x+4x=8x-x | | -8(6b+1)=33-7b | | x+8=-30 | | -6(8m-1)=6-5m | | 6x=5(x+13) | | 8(v-7)+3v=-32+7v | | 1+4(-7+3x)=2x+23 | | 2(6+3a)-8a=-23+5a | | 3M-7+11M+15=-6 | | 1x=1 | | 30x=45(4) | | 1x+-1=0 | | -(8+2x)+6=-x-1 | | -8+7w-7w+8= | | 4X+16X-12=38+10X | | 10x-5+3x=8-x | | -10+5x=5 | | 35-25y+10+35y= |

Equations solver categories